Tinjauan Atas Pengadaan Pembelian Barang Di Bagian Purcashing Pada The Alana Hotel Sentul - Putra, Fawwaz; Supriadi, Yoyon; Srihandoko, Wimpi (Jurnal Ilmiah Pariwisata Kesatuan, 2023)
The Finance and Accounting Department consists of several parts that are interconnected in the goods procurement process, one of which is the Purchasing Department. The role of the Purchasing Department in a hotel is to be responsible for the process of sourcing and procuring goods or services to assist production functions in hotel operational activities with applicable Standard Operating Procedures (SOP). Procurement activities are one of the basic functions of a company or hotel. This procurement function is said to be basic because a company will not be able to operate properly without this function. The next conclusion is that the department concerned with requesting goods has carried out a Purchase Request in accordance with the Standard Operating Procedures that apply at The Alana Hotel Sentul and attached supporting documents, however it is still necessary to pay attention to specifications such as type of goods, brand and quantity for ordering. to suppliers. Keywords: Purchasing, Procurement, Procedure.